CGIAR Initiative on Fragility, Conflict, & Migration: Donor & partner round table highlight reel - Kosec, Katrina; Laderach, Peter; Ruckstuhl, Sandra; Abay, Kibrom A.; Ambler, Kate; Kamanda, Josey (CGIAR System Organization, 2024)
The CGIAR Initiative on Fragility, Conflict, and Migration (FCM) hosted an FCM Showcase: Donor & Partner Round Table on November 6, 2024.